2005
DOI: 10.1038/sj.gene.6364268
|View full text |Cite
|
Sign up to set email alerts
|

The human CD94 gene encodes multiple, expressible transcripts including a new partner of NKG2A/B

Abstract: CD94/NKG2A is an inhibitory receptor expressed by natural killer (NK) cells and a subset of CD8 þ T cells. Ligation of CD94/ NKG2A by its ligand HLA-E results in tyrosine phosphorylation of the NKG2A immunoreceptor tyrosine-based inhibitory motifs, and recruitment and activation of the SH2 domain-bearing tyrosine phosphatase-1, which in turn suppresses activation signals. The nkg2a gene encodes two isoforms, NKG2A and NKG2B, with the latter lacking the stem region. We identified three new alternative transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…The activating or inhibitory function of the heterodimer complex depends on the cytoplasm region of NKG2 molecules. Accordingly, NKG2A and B have immunoreceptor tyrosine-based inhibition motif (ITIM) groups that act as inhibitors (14)(15)(16), whereas NKG2C, NKG2D, and NKG2E lack ITIMs, instead they transmit activating signals (17)(18)(19). NKG2C is associated with a 12 kDa DNA-activating protein (DAP-12), a factor containing an immunoreceptor tyrosine-based activating motif (ITAM) that provides cellular activating signals (17).…”
Section: Introductionmentioning
confidence: 99%
“…The activating or inhibitory function of the heterodimer complex depends on the cytoplasm region of NKG2 molecules. Accordingly, NKG2A and B have immunoreceptor tyrosine-based inhibition motif (ITIM) groups that act as inhibitors (14)(15)(16), whereas NKG2C, NKG2D, and NKG2E lack ITIMs, instead they transmit activating signals (17)(18)(19). NKG2C is associated with a 12 kDa DNA-activating protein (DAP-12), a factor containing an immunoreceptor tyrosine-based activating motif (ITAM) that provides cellular activating signals (17).…”
Section: Introductionmentioning
confidence: 99%
“…As a result of the lack of suitable isoform-discriminating Abs, it remains unknown so far whether the alternative isoforms of the marmoset monkey are indeed expressed as proteins in vivo. However, stalk-lacking isoforms are identified in humans (37) and Old World (36,40) and New World monkeys (this article) and, thus, are evolutionarily conserved for Ͼ43 million years (61). Further support for functional significance of alternatively spliced transcripts comes from studies that revealed substantial variability in mRNA expression of NKG2 genes lacking the stalk and/or the transmembrane region.…”
Section: Discussionmentioning
confidence: 97%
“…3B, glutamine residue) in the CRD region, two CD94 isoforms might be expressed that lack the stalk region. Lieto et al (37) have described corresponding CD94 isoforms in humans. Interestingly, in vitro analyses indicated a preferential association of both stalk-lacking isoforms of human CD94 (CD94-T4) and NKG2A (NKG2B), which could functionally inhibit TCR-mediated signals in Jurkat cells (37).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations